From Loren to Marimar the Philippines media in the 1990's - Coronel, Sheila S. (Quezon City Philippine Center for Investigative Journalism, 1999)
An anthology of 35 PCIJ articles first published in various newspapers. The book traces how, in just a decade, the media in the Philippines got to be as powerful as it is now. It also examines the structure of Philippine newspapers and television, describes Filipino forays into the World Wide Web, and probes such problems as ethics and ownership.
Lords of the press / by Sheila S. Coronel
The cloning of the Sun Star / by Yvonne T. Chua
Death of a journalist / by Howie G. Severino
Dear Xerex / by J.R. Alibutud
The empire strikes back / by Luz Rimban
Bankrupt but (almost) free / by Stella Tirol
The media as kingmaker / by Sheila S. Coronel
Dirty Harry goes to TV / by Luz Rimban
Buying the news / by Yvonne T. Chua and Vinia Datinguinoo
Dissent on the net / by Alecks P. Pabico
Web wet dreams / by Alecks P. Pabico
Electronic campaigning / by Alecks P. Pabico
Keywords: Mass media -- Philippines